302 - The Effectiveness and Safety of Electroconvulsive Therapy for Treatment Refractory Agitation or Aggression in Major Neurocognitive Disorder. (October 2020) - Woo, Simon; Chan, Peter; Waxman, Robyn E; Elmi, Sarah; Musacchio, Mafalda; Wilkins-Ho, Michael; Docherty, Claire
Abstract : Introduction: Fifty to ninety percent of individuals with Major Neurocognitive Disorder (MNCD) have Neuropsychiatric Symptoms (NPS) 1 . Agitation and aggression are amongst the most persistent and treatment-refractory symptom clusters. Patients with these NPS are associated with increased risk of institutionalization, psychotropic medication use, caregiver burden, and mortality 2 . Safe and effective treatments for NPS are lacking. Consensus guidelines emphasize the initial use of non-pharmacologic approaches though supportive evidence is limited 3 . Extensive research has established the safety and efficacy of ECT in elderly patients with depression and other psychiatric conditions 6 . Clinical experience suggests that ECT is a valuable treatment option in MNCD-related treatment refractory NPS cases 7-10 . However, data supporting the efficacy and safety of this practice is scant. Materials and Method: Patients admitted to the geriatric psychiatry inpatient units who meet the inclusion criteria, were recruited from 2 Vancouver sites and 3 unit at Ontario Shores. These patients had an anesthesia consultation to evaluate their safety of going through ECT. Consent was obtained from their substitute decision makers. All patients enrolled are already on psychotropic medications.